The role of internal and external corporate governance mechanisms on firm’s financial performance in Malaysia - Allan Chang (FEP, 2015)
This paper examined six corporate governance variables which are hypothesized to have an influence on firm’s financial performance in Malaysia. The variables encompassed four internal monitoring measures (CEO and chairman of the board, non-executive directors, audit committee and concentrated ownership) with the remaining two variables being external measures (institutional investors and lenders). An empirical study was conducted based on data involving 420 Malaysian listed companies over a four-year period from 2009 to 2012. A combination of cross-sectional and time-series data was employed in the analysis. An econometric model using panel data regression techniques was employed to analyse performance of the firms using both fixed effects and random effects models. Using return on equity as the dependent variable, it was established that CEO duality (an internal monitoring measure) significantly influences the performance of firms. The study showed that a CEO who is also chairman of the board exerts a positive influence on company earnings. It suggests that CEO duality could increase performance of firms when these CEOs dominate the decision-making process in their companies. None of the other monitoring measures relating to independent directors, institutional investors, ownership structures, audit committee and banks played any role in influencing firm performance.